Cost of quality and poor quality - García P., Manuel (2002)
This article describes the quality costs as the quality has evolved, and then analyzes the cost approach and the quality of the new approach that distinguishes the quality and cost of poor quality, shows the most common prevention costs quality, quality assessment and internal and external costs of poor quality. And take into consideration the importance of a partnership between the state and to form a National Entrepreneurship Network Quality, to support the importance of this network I take as an example a study in the State of Israel.